Explanatory Factors of Gestational Diabetes Pedigree Function of Pima Indian Heritage Women - Mahashweta Das; Rabindra N. Das (Internal Medicine, 2022)
Diabetes pedigree function (DPF) predicts diabetes risk based on age and family history, regardless of whether the person is diabetic or not. There is little proof to support the notion that type 2 diabetes (T2D) is a hereditary condition. In real life, it is common for a T2D patient to have T2Ds in one or more family members, such as at least one parent or sibling.1,2 Additionally, it is observed that a subject’s chance of having T2Ds rises in proportion to the number of members of his or her family who have the disease.